African Development at Risk - Pelizzo, Riccardo (African Politics and Policy Newsletter, 2019)
In 2018 Abel Kinyondo, Zim Nwokora and I co-authored a paper entitled ‘Development in Africa’ which was eventually published by World Affairs. In the article we claimed that the development progress that countries in Sub-Saharan Africa had experienced was the result of several factors...
Keywords: African politics